Association of Gestational Age at Coronavirus Disease 2019 (COVID-19) Vaccination, History of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection, and a Vaccine Booster Dose With Maternal and Umbilical Cord Antibody Levels at Delivery. Issue 3 (March 2022) - Yang, Yawei J.; Murphy, Elisabeth A.; Singh, Sunidhi; Sukhu, Ashley C.; Wolfe, Isabel; Adurty, Sanjana; Eng, Dorothy; Yee, Jim; Mohammed, Iman; Zhao, Zhen; Riley, Laura E.; Prabhu, Malavika
Abstract : OBJECTIVE: To describe maternal and umbilical cord blood anti-spike immunoglobulin (Ig)G levels at delivery with coronavirus disease 2019 (COVID-19) vaccination before and during pregnancy and to assess the association of prior severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and a vaccine booster dose with anti-spike maternal and umbilical cord IgG levels. METHODS: We conducted a retrospective cohort study of women with self-reported COVID-19 vaccination (Pfizer-BioNTech, Moderna, or Johnson & Johnson/Janssen), including a booster dose, during or before pregnancy, who delivered at 34 weeks of gestation or more. Maternal and umbilical cord blood samples at delivery were analyzed for semi-quantitative anti-spike IgG. We examined the association between timing of maternal vaccination and maternal and umbilical cord anti-spike levels using a rank sum test. The relationships between a prior history of SARS-CoV-2 infection and maternal and umbilical cord anti-spike IgG levels, and between a booster dose and maternal and umbilical cord anti-spike levels, were also evaluated using a rank sum test. RESULTS: We included data from 1, 359 vaccinated pregnant women, including 20 women who received a booster dose, and 1, 362 umbilical cord samples. Maternal anti-spike IgG levels were detectable at delivery regardless of timing of vaccination throughout pregnancy among fully vaccinated women; however, early third-trimester vaccination was associated with the highest anti-spike IgG levels in maternal and umbilical cord blood. Among women with a history of SARS-CoV-2 infection, maternal and cord blood antibody response achieved with vaccination in early pregnancy was comparable with third-trimester vaccination in pregnant women without a history of SARS-CoV-2 infection. A booster dose in the third trimester was associated with maternal anti-spike IgG levels greater than third-trimester vaccination in women with or without a history of SARS-CoV-2 infection. DISCUSSION: Vaccination against COVID-19 before and throughout pregnancy was associated with detectable maternal anti-spike IgG levels at delivery. A complete vaccination course, prior history of SARS-CoV-2 infection, and a third-trimester booster dose were associated with the highest maternal and umbilical cord antibody levels. Abstract : Coronavirus disease 2019 (COVID-19) vaccination across gestation is associated with detectable maternal and umbilical cord antibodies at delivery.